"Champion" behavior in a community obesity reduction program: Feedback from peers. (February 2017) - Aoun, Samar; Sainsbury, Kirby; Mullan, Barbara; Shahid, Shaouli
Current interventions to reduce obesity have limited success. This study aimed to determine the characteristics of successful champions (non health professional/community leaders) and to assess how these relate to acceptability ratings of an obesity reduction intervention—the Waist Disposal Challenge. A total of 200 peer participants completed questionnaires. Positive ratings of champions' performance were significantly correlated with perceptions of the success and suitability of the Waist Disposal Challenge. The qualitative feedback concurred that the program prompted weight loss and was a positive social experience which resulted in actual behavioral changes. Selecting suitable champions is likely to influence the success of such community health programs.